CONSTITUTIONAL FRAMEWORK FOR MINORITIES WITH SPECIAL REFERENCE TO THE PROTECTION OF CULTURAL AND LINGUISTIC IDENTITIES (International Journal of Food and Nutritional Sciences, 2022)
The process of establishing a council to draft constitution gathered steam during the second World War, whilst the British administration began to negotiate India’s independence. Following a number of steps taken in this regard via the British authorities, the Cabinet Mission Plan was eventually introduced in 1946. It recommended the establishment of a Constituent Assembly and recommended that this assembly establish a committee of advisors upon the rights of citizens, minorities, and excluded areas. According to the Cabinet Mission, the Indian people’s right to secede from the union upon the foundation of a constitution drafted by the constituent assembly would only be granted if sufficient safeguards for minorities rights were put in place. After the formulation of the constituent assembly the matter of minorities protection remained a significant and contentious one, capturing the interest of the members until the assembly finished drafting the constitution in November 1949.